Developing an AHRS tool for a wearable sensor to obtain attitude and heading information - Wada, T.; Leadbetter, R. I.; Rowlands, D. D.; James, D. A. (Journal of Fitness Research, 2016)
Wearable sensors are now widely used in sport and sports science to assess human movement. With sensor fusion, attitude and heading information of the inertial and inertial-magnetic sensor can be obtained. This technique enables measurement of the transition of angles, e.g. lean angle and heading direction of an athlete. This paper describes the development of an attitude heading reference system (AHRS) tool for an inertial-magnetic sensor platfom. The tool includes functions to calculate and animate 3 dimensional attitude of the sensor and to acquire angular displacements around sensor local axes.